1981
DOI: 10.1021/i200014a024
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment from sieve trays operating in the spray regime

Abstract: A correlation is developed to predict entrainment rate for the air-water system on sieve trays operating in the spray regime. The correlation utilizes liquid holdup on the tray as a correlating parameter and is successful in correlating entrainment data for a wide range of tray parameters and gas and liquid loadings. The correlation is extended to account for the effect of system physical properties and is shown to provide predictions of entrainment rate which are in encouraging agreement with the limited expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 5 publications
(26 reference statements)
5
29
0
Order By: Relevance
“…This expression is useful in identifying trends and comparing these to the observations in Kister et al (1981) and Kister and Haas (1988). Equation 30 provides insight and support to their observations.…”
Section: Comparison Of Airwater Froth Regime Entrainment Correlation mentioning
confidence: 89%
See 3 more Smart Citations
“…This expression is useful in identifying trends and comparing these to the observations in Kister et al (1981) and Kister and Haas (1988). Equation 30 provides insight and support to their observations.…”
Section: Comparison Of Airwater Froth Regime Entrainment Correlation mentioning
confidence: 89%
“…sis of the froth flow data, we assumed for the spray regime a correlation format of (33) Kister et al (1981) and others have reported that as liquid rate increases, entrainment can go through a minimum. Porter and Jenkins (1979) proposed that this minimum coincides with the spray to mixed froth/spray transition.…”
Section: E' Ect Of Liquid Inventory and Liquid Jlow Ratementioning
confidence: 99%
See 2 more Smart Citations
“…For sieve trays, entrainment correlations were established by Kister et al. , . Another research group focused on entrainment as well as hydrodynamics of a new type of foam monolithic trays reported by Zhang et al.…”
Section: Introductionmentioning
confidence: 99%